(untitled) (Journal of Nepal Physical Society, 2020)
The absorption coefficient of electromagnetic wave propagating through overdense absorbing plasma is calculated by using Fresnel’s formula. Also, the force acting per unit volume of the electron fluid is calculated along z direction. The Fresnel’s formula is reduced in terms of conductivity and angular frequency so that nature of absorption coefficient with respect to conductivity of plasma and angular frequency of wave is studied, with the assumption that conductivity and angular frequency are two independent terms. By keeping conductivity of plasma constant, it is seen that the absorption coefficient is increased with increase in angular frequency and also absorption coefficient has the lowest value for the highest value of conductivity. At constant angular frequency of incidence, the absorption coefficient is decreased with increase in conductivity and also absorption coefficient has the highest value of angular frequency of incidence. Also the nature of force on the plasma is studied by considering that the conductivity of plasma is very large with compare to angular frequency of incident laser. The expression of absorption coefficient is separated into real and imaginary parts, and then plots are studied with respect to these parts. It is found that in both cases, the force on plasma is existed for short in time and distance, and then damps exponentially. Also, the variation of potential with distance is cleared that the potential is shielded within multiple distance of Debye length.